PENERAPAN PERSONAL SELLING DALAM MEMASARKAN PRODUK PEMBIAYAAN MURABAHAH PADA PT. BANK PEMBIAYAAN RAKYAT SYARIAH MITRA HARMONI KOTA MALANG - Dian Nailiyah, Fani Firmansyah, (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2013)
Recently, many sharia financial institutes stand, either banks general or banks people of islamic finance. PT BPRS Mitra Harmoni Malang City as a new sharia financial institute is demanded to be able to compete to other financial institute, so that the marketting strategyÂ is needed fully. Personal selling is one of marketting method of producttion in order to be able to be pervaded by market. PT BPRS Mitra Harmoni Malang City markets payment product of murabahah by using the personal selling, can stand even more develope. This research it conducted to know how the application of personal selling in marketing murabahahÂ payment product in PT BPRS Mitra Harmoni Malang City. The kind of this research is method qualitative approach descriptive, the researcher describes how processes or steps personal selling conducted PT BPRS Mitra Harmoni Malang City, the technique of data collecttion uses the observation, interview and documentation. Method data analysis that researcher use is method data analysis descriptive. The research result shows that proses or step personal selling which is held in PT BPRS Mitra Harmoni Malang City is Prospecting Approach, Preapproach, Approach, Presentation, Handling Objection, Closing and follow up. Handling Objection which is held PT BPRS Mitra Harmoni Malang City is sales person continue closing sale without asked reservation prospective customers and do not dig the hidden reservation then use the reservation as an opportunity to provide more information and change the mind be a reason to buy.